Lanthanide‐Doped Upconversion Nanoparticles: Emerging Intelligent Light‐Activated Drug Delivery Systems. Issue 7 (15th March 2016) - Bagheri, Ali; Arandiyan, Hamidreza; Boyer, Cyrille; Lim, May
Abstract : The development of drug delivery systems (DDSs) using near infrared (NIR) light and upconversion nanoparticles (UCNPs) has generated intensive interest over the past five years. These NIR‐initiated DDSs not only offer a high degree of spatial and temporal determination of therapeutic release but also provide precise control over the released dosage. Furthermore, these nanoplatforms confer several advantages over conventional light‐based DDSs—NIR offers better tissue penetration depth and a reduced risk of cellular photo‐damage caused by exposure to light at high‐energy wavelengths (e.g., ultraviolet light, <400 nm). The development of DDSs that can be activated by low intensity NIR illumination is highly desirable to avoid exposing living tissues to excessive heat that can limit the in vivo application of these DDSs. This encompasses research in three directions: (i) enhancing the quantum yield of the UCNPs; (ii) incorporation of photo‐responsive materials with red‐shifted absorptions into the UCNPs; and (iii) tuning the UCNPs excitation wavelength. This review focuses on recent advances in the development of NIR‐initiated DDS, with emphasis on the use of photo‐responsive compounds and polymeric materials conjugated onto UCNPs. The challenges that limit UCNPs clinical applications, alongside with the aforementioned techniques that have emerged to overcome these limitations, are highlighted. Abstract : Recent advances in upconversion nanoparticles (UCNPs) as NIR‐initiated controlled drug delivery are highlighed. Surface modification strategies are reviewed alongside with the influence of the laser power intensity and illumination time on the drug release. Three different approaches to engineer biocompatible UCNPs‐assisted drug delivery systems are also discussed in detail.